Step-wise Treatment of Bladder Pain Syndrome: Case Report - Černiauskienė, Aušra; Tubutytė, Geistė; Zaveriuchaitė, Augustina (Lietuvos chirurgija, 2022)
Bladder pain syndrome/interstitial cystitis is a condition characterized by chronic pelvic and bladder pain (lasting longer than 6 months) accompanied by urinary symptoms (urinary frequency, urgency and nocturia). It can have a highly negative effect on the quality of life. The treatment of this disease is impeded by lack of understanding of its etiology. Therefore, treatment recommendations and information about their efficacy are scarce. The American Urological Association recommends a step-wise therapeutic approach starting from mere patients’ lifestyle modification to pharmacological therapy or to even more complex methods, such as intravesical botulinum toxin-A injections. We present here a case of a 60-year old woman, who presented in 2020 with tiresome symptoms characteristic to bladder pain syndrome lasting for two years. Previous treatments with antibiotics, anti-inflammatory, analgesic and anticholinergic medications were unsuccessful; urine culture was negative. During the cystoscopy in our center small bladder capacity and minute glomerulations were observed. Urodynamic tests (cystometry) were performed showing hypersensitive bladder with small capacity. Bladder hydrodistention procedure was performed twice; however the positive effects only lasted up to one month each time. Therefore, it was decided to perform an intravesical botulinum toxin-A injection into bladder trigonal area after which the patient experienced a significant relief in bladder pain, reduced urinary frequency during the day and night and improved quality of life.
Keywords: bladder pain syndrome; interstitial cystitis; botulinum toxin-A injection